Effects on intellectual capital information disclosed in annual reports on market capitalisation: evidence from Bursa Malaysia - Abdulrahman Anam , Ousama; Abdul Hamid, Fatima; Abdul Rashid, Hafiz Majdi (Emerald Group Publishing Limited, 2011)
This paper aims to examine the effects of intellectual capital (IC) disclosure in the annual reports of listed companies in Bursa Malaysia (BM) on their market capitalization (MCAP).